Study on inventory management practices and inventory management performance among pharmacies of public hospitals setting in Malaysia - Fariza, Mahyadin @ Mahidin (2018)
The main purpose of this study was to investigate the relationship between inventory management practices and inventory management performance in Malaysian public hospital pharmacies. Specifically, it aimed at investigating the moderating effect TQM on the relationship between inventory management practices and inventory management performance. The motivation for this study was driven by the inconsistent findings in the literature concerning the relationship between inventory management practices and inventory management performance. Due to these inconsistencies, a new research stream emerged which suggested investigating the effect of possible moderating variables that may better explain such inconsistencies. Accordingly, this study integrated different theories such as the System Theory and the Stakeholder Theory to map and position the possible relationships between the variables in the conceptual framework. The study utilized a survey questionnaire which was randomly distributed to 103 public hospitals in Malaysia, with a 78 percent response rate. The data collected were analyzed by using the Rasch Measurement Model (Winstep3.6 software) and the Partial Least Squared – Structural Equation Modelling (Smart PLS3 software) technique. The results obtained confirmed that the three constructs, namely inventory administration, inventory control and inventory system have to be together to meet the unidimensionality for inventory management practices. Additionally, the results showed that there is a positive relationship, and TQM moderates the relationship between both variables. However, TQM is unable to moderate this relationship in pharmacies at special hospitals. About 49 percent (39 hospitals) had high abilities to perform the items listed in the questionnaire while 51 percent (41 hospitals) were otherwise. These findings have contributed theoretically, practically and methodologically with imperative implications to academicians, policy- makers and pharmacies of public hospitals in Malaysia specifically.